1992
DOI: 10.1128/jb.174.9.2968-2977.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Corynebacterium glutamicum aecD gene encodes a C-S lyase with alpha, beta-elimination activity that degrades aminoethylcysteine

Abstract: S-(beta-Aminoethyl)-cysteine (AEC) resistance was achieved in Corynebacterium glutamicum by cloning a chromosomal 1.5-kb EcoRV-BglII DNA fragment on a multicopy plasmid. DNA sequence analysis of the 1.5-kb DNA fragment revealed an open reading frame (ORF326) which represents the AEC resistance gene, designated aecD. The aecD gene directs the synthesis of a 36-kDa protein which was visualized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The aecD gene is a nonessential gene and mediates AEC resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Table 4 provides a complete overview of the ATs plus some PLP-containing proteins as results from the various approaches based on genome information for C. glutamicum and functional studies. The PLP-containing MetC (AecD) is not an AT, but it has ␤-lyase activity toward cystathionine (27) or the unnatural amino acid S-(2-aminoethyl)-D,L-cysteine (35). We also did not find any AT activity with NCgl2491, which is adjacent in the genome to a putative T-protein of a glycine cleavage system.…”
Section: Vol 187 2005 Activities Of Aminotransferases In Corynebactmentioning
confidence: 72%
“…Table 4 provides a complete overview of the ATs plus some PLP-containing proteins as results from the various approaches based on genome information for C. glutamicum and functional studies. The PLP-containing MetC (AecD) is not an AT, but it has ␤-lyase activity toward cystathionine (27) or the unnatural amino acid S-(2-aminoethyl)-D,L-cysteine (35). We also did not find any AT activity with NCgl2491, which is adjacent in the genome to a putative T-protein of a glycine cleavage system.…”
Section: Vol 187 2005 Activities Of Aminotransferases In Corynebactmentioning
confidence: 72%
“…With the others, a correlation to L-serine is probably less apparent (see Discussion). Most interestingly, the cystathionine ␤-lyase mRNA level (metC) is increased 2.4-fold, and the respective enzyme of L-methionine synthesis (24), catalyzing a ␤-elimination reaction, has been reported to have a broad substrate specificity in C. glutamicum and in E. coli, also reacting with L-cysteine, which is structurally related to L-serine (1,45,59).…”
Section: Resultsmentioning
confidence: 99%
“…A routine check for protein homology revealed that the deduced amino acid sequence of MalY (24) showed small but significant homology (22.5% identity) to the sequence of the AecD protein of C. glutamicum, an enzyme that, when overproduced, confers resistance to S-2-aminoethyl-L-cysteine (AEC; also called thiolysine) in this bacterium (27). AecD has been identified as a ␤C-S lyase forming ammonia and pyruvate from amino acids containing a ␤C-S linkage (27). The availability of the MalY protein in purified form allowed us to test the enzymatic activity of MalY as a ␤C-S lyase.…”
Section: Resultsmentioning
confidence: 99%